2017
DOI: 10.3138/jvme.0615-097r
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Beliefs about Disclosure of Mental Health Issues: A Qualitative Study

Abstract: In 2012 the United Kingdom's General Medical Council (GMC) commissioned research to develop guidance for medical schools on how best to support students with mental illness. One of the key findings from medical student focus groups in the study was students' strong belief that medical schools excluded students on mental health grounds. Students believed mental illness was a fitness to practice matter that led to eventual dismissal, although neither personal experience nor empirical evidence supported this beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Student youth are considered as a specific group of people, which has its own peculiarities in the way of life, value orientations, and standards of behaviour and motives of activity. The social significance of young people's health is due to the fact that they represent the closest reproductive, intellectual, economic, social, political and cultural reserve of society (Gorelov, 2009;Winter, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Student youth are considered as a specific group of people, which has its own peculiarities in the way of life, value orientations, and standards of behaviour and motives of activity. The social significance of young people's health is due to the fact that they represent the closest reproductive, intellectual, economic, social, political and cultural reserve of society (Gorelov, 2009;Winter, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…looked into the barriers preventing medical students presenting in the time of need . They found that medical students firmly believed that once a mental health disclosure was made, a fitness to practice proceeding would be opened, with the aim of removing them from the course; however, on further questioning the medical students were unable to support this claim with any evidence . Therefore, increasing knowledge and awareness of the actual process that takes place is a key step towards increasing the uptake of mental health and well‐being services by medical students.…”
Section: Discussionmentioning
confidence: 99%
“…One of the core reasons is the belief that disclosing information on their mental health would lead to disciplinary proceedings. Therefore, this fear of being investigated in fitness to practice proceedings stops students from presenting early . There is also stigma associated with mental health and because of this some medical students feel that it is a sign of weakness if they were to seek medical help for mental health problems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researches by the scientists [5,6,7,8] have confirmed the positive effect of the exercises on the condition of all systems of life support of an organism and, accordingly, on the improvement of physical condition and health indicators of the students. To achieve a positive effect, you need to be engaged regularly and systematically.…”
Section: Introductionmentioning
confidence: 99%